A new hybrid in Arab politics: Unstable authoritarianism - Rasmus Alenius Boserup; Jakob Wichmann (Danish Institute for International Studies (DIIS), 2015)
While the recent collapse of political order in the Arab World calls for short term security politics, Europe has a long-term interest in remaining steadfast in its push for political reform. In a new DIIS report, Rasmus Alenius Boserup and Jakob Wichmann explore the trajectory of the collapse of political order in the Arab World after the uprisings of 2011 and provide a series of general pointers for Western and Arab policy makers. Providing empirical evidence from a host of Arab countries including Egypt, Algeria, Syria, Libya and Iraq, the report identifies the contours of a new hybrid in Arab authoritarian governance - "Unstable Authoritarianism" - and provides a series of reflections about the possible policy responses this should be met with. A central point in the report is that while the current instability and reshaping of authoritarian governance in the region legitimately calls for anti-terrorism and security politics, the long-term development of an alternative governance model remains pivotal for Europe's long-term security concerns.
Keywords: 300